ASUHAN KEPERAWATAN PADA NY.T G1P0A0 TRIMESTER III DENGAN LOW BACK PAIN DI WILAYAH PANCORAN, JAKARTA SELATAN - Irena Adibah Surapati, (2023)
Background: Pregnancy is a very important and special phase that is experienced by women, during the process of pregnancy various changes are experienced by women both physically and psychologically. During the 2nd and 3rd trimesters of pregnancy, the most common problem in pregnant women is low back pain. Lower back pain has a negative impact on pregnant women, especially affecting daily activities such as sleep, appetite and concentration. If left untreated, low back pain has the risk of developing chronic back pain which will later be fatal and difficult to treat if muscle and pelvic stability are not restored after delivery. This research was conducted to determine lower back pain and how to deal with lower back pain with nursing care for pregnant women who experience low back pain. Method: this research was conducted using the nursing care case study method in Ny. T with low back pain from 13 February to 15 February 2023. Data collection was carried out through interviews, observation and documentation. Results: The nursing diagnosis is acute pain associated with physiological (musculoskeletal) injury agents. Nursing interventions carried out are identification of location, characteristics, duration, frequency, quality and intensity of pain, identification of pain scale, identification of factors that aggravate and relieve pain, identify the effect of pain on quality of life, provide informacological techniques to reduce pain, facilitate rest and sleep , recommend monitoring pain independently, recommend non-pharmacological techniques to reduce pain. Implementation is carried out in accordance with nursing interventions that have been made and carry out nursing evaluations. Within 3x24 hours the acute pain problem was resolved. Conclusion: The treatment given to Mrs. T based on nursing care can be resolved, Mrs. T has reduced pain with a scale of 3 and Ny. T can independently implement actions to deal with the pain that has been given. Keywords: Pregnancy, Low Back Pain, Nursing Care